Recurrent ventricular tachycardia: a case-series report of three cardiac radioablation (Revista de Física Médica, 2023)
This report includes the most relevant parameters that can influence the final result of cardiac ablation treatments with radiotherapy treated at our institution since 2021 to date. These parameters are linked to patient comorbidity, CTV definition, immobilization, IGRT and treatment plan.
Keywords: Cardiac radiosurgery; cardiac radio ablation; ventricular tachycardia; SBRT; overall survival